2023
DOI: 10.1002/jcp.31027
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 6 ameliorates bleomycin‐induced pulmonary fibrosis via activation of lipid catabolism

Abstract: Pulmonary fibrosis is a chronic and serious interstitial lung disease with little effective therapies currently. Our incomplete understanding of its pathogenesis remains obstacles in therapeutic developments. Sirtuin 6 (SIRT6) has been shown to mitigate multiple organic fibrosis. However, the involvement of SIRT6‐mediated metabolic regulation in pulmonary fibrosis remains unclear. Here, we demonstrated that SIRT6 was predominantly expressed in alveolar epithelial cells in human lung tissues by using a single‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Notably, peroxisome proliferator-activated receptor α (PPARα) has been identified as a critical mediator of SIRT6’s effects on lipid catabolism, anti-inflammatory response, and anti-fibrotic signaling. These findings suggest that targeting the SIRT6-PPARα-mediated lipid catabolic pathway holds promise as a potential therapeutic strategy for pulmonary fibrosis and related disorders [ 31 ]. In addition, other studies have demonstrated that SIRT6 inhibits NF-κB signaling pathway and blocks TGF-β1-induced lung myofibroblast differentiation [ 95 , 124 ].…”
Section: Fibrosismentioning
confidence: 99%
“…Notably, peroxisome proliferator-activated receptor α (PPARα) has been identified as a critical mediator of SIRT6’s effects on lipid catabolism, anti-inflammatory response, and anti-fibrotic signaling. These findings suggest that targeting the SIRT6-PPARα-mediated lipid catabolic pathway holds promise as a potential therapeutic strategy for pulmonary fibrosis and related disorders [ 31 ]. In addition, other studies have demonstrated that SIRT6 inhibits NF-κB signaling pathway and blocks TGF-β1-induced lung myofibroblast differentiation [ 95 , 124 ].…”
Section: Fibrosismentioning
confidence: 99%
“…The authors also discussed the metabolic pathways producing these four-carbon acyl-CoAs which regulate lysine acylation and deacylation, and functions of these lysine acylation (Fang & Li, 2023). Another study in this special issue reported new role of SIRT6-mediated metabolic regulation in pulmonary fibrosis (He et al, 2023). He et al (2023) discovered that SIRT6 protected against bleomycin-induced injury of alveolar epithelial cells and reduced pulmonary fibrosis of mice in vivo.…”
mentioning
confidence: 99%
“…Another study in this special issue reported new role of SIRT6-mediated metabolic regulation in pulmonary fibrosis (He et al, 2023). He et al (2023) discovered that SIRT6 protected against bleomycin-induced injury of alveolar epithelial cells and reduced pulmonary fibrosis of mice in vivo. SIRT6 reduced bleomycin-induced ectopic lipotoxicity by enhancing lipid degradation to increase the energy supply and decrease lipid peroxides.…”
mentioning
confidence: 99%
See 2 more Smart Citations